2020
DOI: 10.1109/jstars.2020.3000391
|View full text |Cite
|
Sign up to set email alerts
|

Generic Performance Simulator of Spaceborne GNSS-Reflectometer for Land Applications

Abstract: Nowadays, the space missions employing the GNSS-Reflectometry (GNSS-R) are UK TDS-1, NASA CYGNSS, and the Chinese BuFeng-1A/B twin satellites, part of the first Chinese global navigation satellite system reflectometry (GNSS-R) satellite mission. They provide Delay-Doppler Map (DDM) measurements reflected from the land as well as the ocean. Using land reflected DDMs, several studies have been conducted to retrieve land geophysical parameters, such as soil moisture and biomass. Despite the clear dependence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…In the previous sections, it was shown that the sensitivity of the calibrated reflectivity to Soil Moisture is non-linear and varies with the Soil Moisture value (Figure 1) [16]. Linearized retrieval approaches must be cautious in order not to introduce biases and other artifacts.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the previous sections, it was shown that the sensitivity of the calibrated reflectivity to Soil Moisture is non-linear and varies with the Soil Moisture value (Figure 1) [16]. Linearized retrieval approaches must be cautious in order not to introduce biases and other artifacts.…”
Section: Discussionmentioning
confidence: 95%
“…As it can be appreciated in Figure 1, computed using a comprehensive GNSS-R simulator [16], assuming a flat soil surface and no vegetation, the variation of the peak of the DDM (Delay and Doppler Map) with respect to SM is highly non-linear. Depending on the range of soil moisture values encountered in the field experiments, different slopes can be found if a linear approximation is assumed to compute the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid specular points with poor elevations, a mask was set to 20 o of elevation (Eq. 1) according to data obtained from previous missions and studies [48], as a compromise between signals of opportunity that would be acquired and the quality of the measurements. Thus, for each plane in the world and every 10-second window during months of data, 5-12 specular points (belonging to the different GPS satellites in view) were calculated with a precision under 10 meters.…”
Section: A Simulationmentioning
confidence: 99%
“…The effect of topography is also very different when comparing airborne to spaceborne receivers [48,54]. The specular reflection corresponds to scattering processes in which waves from a single direction are reflected into a single reflected direction.…”
Section: B Comparison To Cubesat Receiversmentioning
confidence: 99%
“…The invention of the Global Navigation Satellite System (GNSS) was pinnacle in enabling accurate location information for many application and thus brought tremendous convenience to human life [1]. With the upgrading of new generation navigation systems such as the Cyclone Global Navigation System (CYGNSS) in the United States, Global Navigation Satellite System (GLONASS) in Russia, TechDemoSat-1 (TDS-1) in the UK, Galileo GNSS for the European Union, BuFeng-1A/B twin satellites for China and the application of these technologies makes positioning and navigation easier than ever especially for outdoor environments [1]. However, with this continuous expansion and increased uptake for Industrial Internet of Things (IIoT)s, the application of Indoor Positioning Services (IPS) including commercial applications such as logistics, tracking, localize and fetch in warehouses, navigation of Unmanned Ground Vehicles (UGVs) etc.…”
Section: Introductionmentioning
confidence: 99%